Viral and Bacterial Diseases in Broiler Chicken Farms at the Area of Banyumas District - Hastuti, S; Yuwono, E (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
Abstract. Efforts to control viral and bacterial diseases in poultry broiler should always be done by various efforts. Maintenance of strict management, implementation and administration of vaccines and bio security program are some efforts that are often done by farmers in order to eliminate viral and bacterial diseases. The purpose of this study was to determine the type of pathogenic viruses and bacteria that often infect broiler chickens and how to make efforts to control the broiler chicken farms in the subdistricts of Kedungbanteng and Baturraden, district of Banyumas. The research method was survey on broiler chicken farmers in the areas of Baturraden and Kedungbanteng of Banyumas district. Gradual cluster sampling was used in this study. 11 broiler chicken farms with various breeds were involved. The current study found that types of bacterial disease that infected broiler chicken farms in the subdistricts of Kedungbanteng and Baturraden were Chronic Respiratory Disease (CRD) and Colibacilosis, whereas viral diseases that infected were the Infectious Bursal Disease (IBD/Gumboro) and New Castle Disease (ND), although the prevalence rate was low. The efforts to control the main virus diseases, IBD and ND, succeeded in pressing the two diseases sould be implemented.Key Words: viral disease, bacterial disease, broiler chicken farmS Hastuti and E Yuwono/Animal Production 13(3):198-206 (2011)